Mind–body-medicine in oncology—from patient needs to tailored programs and interventions: a cross-sectional study - Leonhardt, Jonas; Winkler, Marcela; Kollikowski, Anne; Schiffmann, Lisa; Quenzer, Anne; Einsele, Hermann; Löffler, Claudia (Frontiers in Psychology, 2023)
Introduction: National and international guidelines recommend early integration of evidence-based multimodal interventions and programs, especially with a focus on relaxation techniques and other Mind-Body-based methods to maintain the quality of life of oncology patients, improve treatment tolerability, and promote healthy lifestyle behaviors. Consequently, we aim to understand what drives patients and how they navigate integrative medicine to best advise them. This study aimed to detect possible topics of particular interest to patients and identify the patient groups that could benefit most from further programs. Furthermore, we aimed to investigate if patients are open-minded towards integrative oncology concepts and learn about their motivational level to maintain or change behavior. Methods: Between August 2019 and October 2020 we surveyed patients undergoing oncological therapy in a university oncological outpatient center using a custom-developed questionnaire based on established Mind-Body Medicine concepts. Results: We included 294 patients with various cancers. More than half reported problems sleeping through (61%) and 42% felt stressed frequently, invariably rating this as detrimental to their health. Moreover, a slight majority (52%) felt physically limited due to their disease and only 30% performed defined exercise programs. Women were significantly more likely to feel stressed and reported with alarming frequency that they often feel “everything was up to them”. The 40-65-year-olds reported significantly less restful sleep, more stress and were more dissatisfied with their situation. However, this group already used natural remedies most frequently and was most often motivated to use relaxation techniques in the next 6 months. The lower the perceived individual energy level (EL), the less frequently patients did sport, the more frequently they felt their disease impaired their activity, mostly feeling stressed and tense. We also found significant associations between negative emotions/thoughts and the variables “sleep”, “use of relaxation techniques”, “personal stress perception”, and “successful lifestyle modification”. Conclusion: Mind-Body programs that focus on patient’s individual resources, with tools to explore impairing patterns of self-perception and cognitive biases, can be a valuable resource for oncology patients and should therefore be part of an integrative medical treatment concept.